ETHNO-PHYTO-VETERINARY MEDICINES IN NORTHERN PAKISTAN - G. M. Shah; M. Ahmad; M. Arshad; M. A. Khan; M. Zafar; S. Sultana (Journal of Animal and Plant Sciences, 2012)
The Mountains of District Abbottabad (Northern Pakistan) are endowed with a diverse plant wealth. The current communication gives the results of an ethnobotanical survey of the area for documentation of medicinal plants used to cure different ailments of animals. In this region Bakerwals and other migratory herders utilize herbal remedies for the treatment of their livestock. Periodic field trips were undertaken during 2001-2005 to various rural and distant areas of district Abbottabad. Information on the utilization of local plants used for curing common animal/livestock ailments was obtained through interviews of herders, shepherds, and others that work with farm animals. The treatment inventory of a healer typically includes 7-10 types of diseases. The most frequent diseases are diarrhoea, after birth retention, prolapse of uterus, constipation, foot and mouth rot, colic, indigestion, blood in urine and fever, etc. A total of 54 plants within 34 families were identified for the treatment of a variety of animal diseases.
Keywords: Ethnobotany; Flora; Veterinary diseases; Abbottabad; Pakistan